PENGARUH GENDER DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (STUDI KASUS PT XYZ) - Jenia Nur Soelistyoningrum (ESENSI: Jurnal Manajemen Bisnis, 2020)
The purpose of this empirical study is to analyze the effect of gender and leadership style to the performance of employee. The research samples consist of 76 respondents. This research uses primary data that obtained by distributing questionnaires to PT XYZ employees who meet the criteria that have been determined through purposive sampling. This research uses multiple linear regression analysis. The results show that gender and leadership style positively influence the performance of employee.